Caracterização da microbiota lática, não lática e utilização do tratamento ôhmico para processamento de queijo de coalho - SANTOS NETO, Torquato Marques dos (2010)
The curdle Cheese traditionally is produced in artisan way in small properties located in the States northeast Brazilian from raw milk without addition of cultures starters. The objective of this work was to characterize microbiot of the curdle cheese produced from raw milk of the milk basin of the State of Pernambuco, north-eastern of Brazil and to test alternative the ohmic heating while of pasteurization of the cow milk to be used for the production of the curdle cheese. A total of 500 bacteries had been isolated in the 5 studied cities, being that 370 samples (74%), had presented characteristics of acid lactic bacteries (BALs). Amongst the BALs the Lactococcus lactis presented the frequency of 78,38% in relation to excessively; Enterococcus faecalis (18.92%) and Leuconostoc spp (2.77%). The BALs identified by morphotintorials testsand biochemists (84.21%) had been confirmed by sequencialting of the gene 16S rRNA. The Bacillus cereus enters the not acid lactic bacter got 42.31% of frequency of the averages observed in the studied cities. After to be dealt with by ohmic heating, was observed the absence to fosfatasis and presence to peroxidasis beyond the reduction the microbial load. From the joined Portary in the 146 was evidenced that the cheeses if do not adjust the denomination “average humidity” (of 36,0 45,9g/100g) defined for the curdle cheese for the Resolution in the 7 of 28 of November of 2000 of the Ministry of Agriculture and the Supplying, characterizing themselves as cheeses of high humidity (between 46,0 and 54,9g/100g, in accordance with, of 07 of March of 1996). It was a bigger acceptability of the cheese produced from ohmic if compared milk with the cheese produced from pasteurized milk. The knowledge of microbiot of theartisan curdle cheese could be an initial step to be identified as product of geographic indication (GI). The results indicate that the ohmic heating could be introduced in the process of pasteurization of milk without influencing its quality negative.